NARRATIVES OF RESISTANCE AND LIBERATION: ALICE WALKER'S CONTRIBUTION TO INTERSECTIONAL JUSTICE LITERATURE AND DISCOURSE - Wajiran Wajiran; Erik Tauvani Somae; Laga Adhi Dharma (Lire Journal (Journal of Linguistics and Literature), 2025)
This paper examines Alice Walker's literary contributions and activism through intersectional analysis in the novel The Color Purple. As a black female writer born and raised in a racist and patriarchal society, Walker uses her works to explore the oppression based on race, gender, and social class experienced by African-American women. Through the theoretical lens of black feminism and womanism, this paper examines how The Color Purple portrays the transformation of the main character, Celie, from a state of oppression to self-empowerment through female solidarity and economic empowerment. Home and business ownership in the novel become important symbols that mark Celie's social, spiritual, and economic transformation. By presenting the voices of black women who have been marginalized, Walker not only writes literary works but also engages in social criticism and fosters a discourse of intersectional justice. This work demonstrates that literature can serve as a tool of liberation and resistance, as well as a space for articulating the collective experiences of oppressed women. Through this analysis, this paper highlights Alice Walker's significant role in the realm of literature and contemporary feminist thought